Catalytic performance of Co, Fe on MCM-41 synthesized from illite waste for gasification of torrefied cassava rhizome. (November 2021) - Sirinwaranon, Punchaluck; Sricharoenchaikul, Viboon; Atong, Duangduen
Abstract: The catalytic gasification of torrefied cassava rhizome (TCR) with metals (Co, Fe) on MCM-41 was studied throughout this work. The focus of this research is to synthesize, evaluate and analyze the performance of ordered mesoporous MCM-41 employing illite clay waste as silica and aluminum sources under hydrothermal pressure condition using cetyltrimethylammonium bromide as structure template. The characterization of catalysts was carried out by low angle X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), and N2 physisorption isotherm which indicated the formation of well-ordered MCM-41 mesoporous materials, high surface area (952 m 2 /g) and corresponds to a type IV isotherm of hysteresis loop, respectively. Co and Fe were deposited on synthesized MCM-41 surface by impregnation method. The catalytic performance was tested in an ex-situ gasification process at 700 °C. The 5Co/MCM-41 catalyst significantly increased the carbon conversion from 68.63% to 77.30% while using 5Fe/MCM-41 catalyst yielded the highest H2 /CO ratio of 0.66, hydrogen conversion of 26.80% and gas heating value of 10.72 MJ/kg. The results indicated that the illite waste may be converted to high-value zeolite material while TCR is a potential greener fuel feedstock for gasification. This novel method to synthesize the MCM-41 from illite clay waste utilized doping of cobalt and iron metal catalyst to increase the efficiency of gasification of TCR.